Evaluation of antifungal effect of amphotericin B in comparison with nystatin on Candida species derived from patients undergoing head-and-neck radiotherapy (Dental Research Journal)
Background: There is ample evidence showing the development of nystatin-resistant strains in patients undergoing malignancy treatment. Amphotericin B is a polyene antifungal drug that combines with ergosterol to cause cell death and is more effective on fungal species than routine antifungals such as nystatin. This study aimed to compare the effect of nystatin and amphotericin B on fungal species isolated from patients before and during head-and-neck radiotherapy. Materials and Methods: This in vitro experimental study was performed on samples isolated from patients undergoing head-and-neck radiotherapy before and during radiotherapy at Sayed al-Shohada Hospital in Isfahan, Iran. The isolates were identified by polymerase chain reaction-restriction fragment length polymorphism. Antifungal effects were determined by the microdilution method based on clinical and laboratory standards institute standards and minimum inhibitory concentration (MIC), minimum lethal concentration (MFC), drug sensitivity, and resistance were measured. The data were analyzed by SPSS version 22 (level of significance: 0.05). Results: Before radiotherapy, all albicans strains were sensitive to nystatin, whereas 71.4% were sensitive to amphotericin B. After radiotherapy, Candida albicans strains were 100% sensitive to nystatin and 75% sensitive to amphotericin B. Conclusion: The present study showed that before radiotherapy, all species isolated from patients, including C. albicans, C. tropicalis, and C. glabrata, were sensitive to nystatin, whereas a percentage of albicans species showed resistance to amphotericin B. In the 2nd week of radiotherapy, the same as before radiotherapy, all species isolated from patients were sensitive to nystatin, whereas a percentage of albicans species showed resistance to amphotericin B. In general, the current study showed that before and after radiotherapy, the antifungal effect of nystatin is greater than amphotericin B.